The multipart film: extended anthropological analysis and non-textual forms. Issue 1 (1st January 2021) - Grimshaw, Anna
Abstract : Ethnographic filmmakers have long struggled to make a case for the intellectual seriousness of their work. Although this is changing, especially in certain areas of the discipline (sensory ethnography, collaborative research, for example), the kinds of inquiry the medium of film facilitates is often not clear to those whose familiarity lies exclusively with written argument-based forms. Another problem for the ethnographic filmmaker, hitherto unacknowledged, is the dominance of the self-standing film and the limitations it places on the analytical possibilities of their medium. This article explores the potential of a multi-part work as an important alternative. Drawing on selected films of David MacDougall (To Live With Herds, the Turkana Trilogy and the Doon School series), it highlights his experimentation with academic form. Offering fresh insight into MacDougall's contribution to an intellectually ambitious agenda for filmmaking in anthropology, it raises questions about the nature and scope of analytical work pursued outside of the discipline's established textual conventions. How might multipart work offer an important example of how film can function as a medium for extended anthropological inquiry?